The effect of terrain on entheseal changes in the lower limbs - Acosta, M. A. (2017)
One of the main factors involved in entheseal changes (EC) aetiology may be related to the physiological limits of biomechanical loading fixed during bone development, such that higher load during childhood and the adolescent growth spurt leads to a lower frequency of EC during adulthood. In this sense, it is possible that ECs may be related to overloading beyond an individual’s normal physiological limits as established during childhood and adolescence. This meta-analysis tested this aetiological possibility by studying the influence of terrain on the entheses of the lower extremities. The hypothesis is that individuals who inhabited rugged terrain have lower EC than those living in flat terrain. This is because biomechanical loads associated with rugged terrain will lead to a higher normal capacity (defined during skeletal development) mitigating the probability of overloading compared to those living in flat terrain who will therefore have a higher frequency of ECs. To test this, papers reporting EC frequencies in the lower limbs were analysed alongside the local terrain. Terrain was defined into two categories: flat or rugged based on altimetry profile, i.e. the average elevation gains and losses along four specific paths (North-South, East-West, Northwest-Southeast, Southwest-Northeast). Odds ratios were calculated to compare rugged and flat terrain. The overall results are consistent with the hypothesis that overloading is a factor in EC aetiology. However, when the analysis is conducted by sex and side, this general trend does not always occur. Limitations such as the lack of standardized age ranges could be affecting the outcome, i.e. older individuals have a higher frequency of ECs. The findings of this analysis suggest that the theoretical assumptions associated with the cause of ECs require further testing and evaluation.